Motion in Augmented Reality Games: An Engine for Creating Plausible Physical Interactions in Augmented Reality Games. (29th July 2010) - Mac Namee, Brian; Beaney, David; Dong, Qingqing
Abstract : The next generation of Augmented Reality (AR) games will require real and virtual objects to coexist in motion in immersive game environments. This will require the illusion that real and virtual objects interact physically together in a plausible way. The Motion in Augmented Reality Games (MARG) engine described in this paper has been developed to allow these kinds of game environments. The paper describes the design and implementation of the MARG engine and presents two proof-of-concept AR games that have been developed using it. Evaluations of these games have been performed and are presented to show that the MARG engine takes an important step in developing the next generation of motion-rich AR games.